Electronic Terrorism is Legal Challenges and Illegal Practices - Abdalla, Abdelrahman; Almidfa, Halima (Journal of Legal Sciences, 2026)
This study investigates the modern threat of cross-border electronic terrorism, which significantly impacts state security and is linked to various factors. It highlights the challenges in controlling and prosecuting electronic terrorism due to differing international criminal procedures for terrorist activities like inspection, investigation, and evidence collection. The study also finds that electronic terrorism, reliant on computers and the internet, differs significantly from traditional methods, making it harder to regulate and prosecute. This challenge is worsened by inadequate cybersecurity and inconsistent laws globally.